2014
DOI: 10.1002/jbm.b.33201
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun vascular grafts with improved compliance matching to native vessels

Abstract: Coronary artery bypass grafting (CABG) is one of the most commonly performed major surgeries in the United States. Autologous vessels such as the saphenous vein are the current gold standard for treatment; however, synthetic vascular prostheses made of expanded poly(tetrafluoroethylene) (ePTFE) or poly(ethylene terephthalate) (PET) are used when autologous vessels are unavailable. These synthetic grafts have a high failure rate in small diameter (<4 mm) applications due to rapid re-occlusion via intimal hyperp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
78
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 48 publications
3
78
0
1
Order By: Relevance
“…In accordance, histological staining showed wavier collagen fibers in ASC-TEVS than in DF-TEVS. The compliance of ASC-TEVS (3.72%/100 mmHg) was still lower than native arteries, which range from 4.5 to 16%/100 mmHg in the literature [36][37][38], but it was higher than most synthetic material [39,40]. Furthermore, due to the biological nature of the TEVS, an in vivo remodeling is likely to further improve their compliance [31,37].…”
Section: Discussionmentioning
confidence: 82%
“…In accordance, histological staining showed wavier collagen fibers in ASC-TEVS than in DF-TEVS. The compliance of ASC-TEVS (3.72%/100 mmHg) was still lower than native arteries, which range from 4.5 to 16%/100 mmHg in the literature [36][37][38], but it was higher than most synthetic material [39,40]. Furthermore, due to the biological nature of the TEVS, an in vivo remodeling is likely to further improve their compliance [31,37].…”
Section: Discussionmentioning
confidence: 82%
“…Although considerably lower than natural vessels, it was also twice as large as the highest blood pressure recorded in humans (370 mm Hg) 94. Compliance and burst pressure are often inversely related, which underlines the difficulty of engineering vascular prostheses 49. Hence, a compromise was found between compliance and burst strength achieved by 150 µm WT PLC 70:30 tubes.…”
Section: Discussionmentioning
confidence: 96%
“…The 150 µm WT PLC 70:30 tube, which had the closest compliance match to the porcine arteries, exhibited a burst strength of 769 ± 9 mm Hg. It is often reported that a vascular prosthesis should exceed the value of saphenous veins (1599 ± 877 mm Hg [89] ) or ten times the systolic pressure ( P Syst = 120 mm Hg) 49,92,93. Although considerably lower than natural vessels, it was also twice as large as the highest blood pressure recorded in humans (370 mm Hg) 94.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7, 17, 19 To this end, earlier idealized geometric models are giving way to those with unprecedented structural detail. 9, 17, 25 These pursuits are facilitated by the increased availability of micro-computed tomography (μCT), which, with voxel resolution as fine as 9–17 μm, 11 has rapidly become a gold-standard against which other structural imaging modalities are evaluated.…”
Section: Introductionmentioning
confidence: 99%